A Digest of the Laws of Pennsylvania, from the Year One Thousand Seven Hundred to the Sixth Day of June, One Thousand Eight Hundred and Eighty-Three, at 1451, Railroads, pt. 10, § 194 (11th ed., vol. 2, 1885) - (:unkn) unknown (My University, 1876)
If any person shall break, pull down or destroy any part or parts of said inclined plane, or other property of the said corporation, or shall willfully obstruct the passage in or to said inclined plane, or any part or parts thereof, each such person shall forfeit and pay to the said corporation the sum of ten dollars for each and every such offence, to be recovered as other debts of a like amount are recoverable; and if any person shall be guilty of carrying a lighted cigar or pipe, or carrying fire into the station-houses and buildings of the corporation, in any manner except in a lantern, or shall discharge any pistol or gun, or any fire-works in or near the building of the said company
Keywords: DISCHARGE